Optimization of the educational process of medical higher edu-cation institutions through the information and educational environment - Murzina, O. A.; Raznatovska, O. M.; Pototska, O. I.; Nahorna, N. O.; Мурзіна, Олена Анатоліївна; Разнатовська, Олена Миколаївна; Потоцька, Олена Іванівна; Нагорна, Наталія Олександрівна; Мурзина, Е. А.; Разнатовская, Е. Н.; Потоцкая, Е. И.; Нагорная, Н. А. (My University, 2020)
Improving the effectiveness of training of future highly qualified personnel requires the improvement of existing and search for new forms and methods for organizing the educational process. Such approach requires the use of complexes of technical and didactic means that ensure the interconnection between classroom and non-classroom forms of the educational process. Objective. To analyze the existing conditions for the implementation of information and educational environment. Methods. Analysis of theoretical sources on the problem of the use of the information and educational environment in higher medical education, studying and generalization of leading experience in teaching student courses using information and communication technologies. The analysis of the results of the efficiency of implementation of the educational and informational environment has been carried out on the departments of phthisiology and pulmonology, histology, cytology and embryology, medical physics, biophysics and higher mathematics and analytical chemistry. Results. The article presents certain results of the work of lecturers concerning the development and use of the informational and educational environment in the context of continuing learning of present-day information-oriented society. Creating information and educational environment that supplies interaction between lecturers and students in classroom through interactive forms of communication on the basis of edХ platform promotes the optimization of the learning process. The basic principles of providing innovative approaches, methods, technologies of the uniform informational and educational environment of higher education medical institutions are substantiated. The necessity of disclosing the experience of higher education institutions regarding the creation of the informational and educational environment as part of the optimization of the student's educational process is emphasized. The experience of using new learning form confirmed the simplicity and interactivity of interaction of the student and the lecturer, gives the wide opportunities for learning process arrangement, enables the student to model learning process individually, as well as new forms of learning process supervision. Conclusion. In our opinion, online courses based on edX platform facilitate the optimization of the learning process in higher education institutions. The prospect of further work is the continuation of the development and implementation of the online course for students on edX platform in the learning process. Підвищення ефективності професійної підготовки майбутніх висококваліфікованих кадрів потребує удосконалення існуючих та пошуку нових форм і методів організації навчального процесу. Такий підхід потребує використання комплексів технічних і дидактичних засобів, які забезпечують взаємозв’язок аудиторної та позааудиторної форм занять. Мета. Проаналізувати існуючі умови реалізації інформаційно-освітнього середовища. Методи. Аналіз теоретичних джерел з проблеми використання інформаційно-освітнього середовища у вищій медичній освіті, вивчення та узагальнення передового досвіду викладання студентських курсів з використанням інформаційно-комунікаційних технологій. Аналіз результатів ефективності впровадження освітньо-інформаційного середовища проведено на кафедрах фтизіатрії та пульмонології, гістології, цитології та ембріології, медичної фізики, біофізики та вищої математики та аналітичної хімії. Результати. У статті представлені певні результати роботи викладачів стосовно розробки та використання інформаційно-освітнього середовища в контексті неперервної освіти сучасного інформаційного суспільства. Інформаційно-освітнє середовище, що забезпечує взаємодію викладачів та студентів у класі через інтерактивні форми спілкування на платформі edХ, сприяє оптимізації навчального процесу. Обґрунтовано основні засади забезпечення інноваційних підходів, методів, технологій єдиного інформаційно-освітнього середовища вищого навчального медичного закладу. Підкреслена необхідність розкриття досвіду вищих навчальних закладів щодо створення інформаційно-освітнього середовища, як складової оптимізації навчального процесу студентів. Досвід використання нової форми навчання підтвердив простоту та інтерактивність взаємодії студента і викладача, дає широкі можливості для організації навчальної діяльності, дозволяючи студенту самостійно моделювати свій процес навчання, а також нові форми контролю навчальної діяльності. Підсумок. На нашу думку, online курси на платформі edX сприятимуть оптимізації навчального процесу вишу. Перспективою подальшої роботи ми вбачаємо в розробці та впровадженню в навчальний процес online курсів для самостійної роботи студентів на платформі edX. Повышение эффективности профессиональной подготовки будущих высококвалифицированных кадров требует совершенствования существующих и поиска новых форм и методов организации учебного процесса. Такой подход требует использования комплексов технических и дидактических средств, обеспечивающих взаимосвязь аудиторной и внеаудиторной форм занятий. Цель. Проанализировать существующие условия для реализации информационно-образовательной среды. Методы. Анализ теоретических источников по проблеме использования информационнообразовательной среды в высшем медицинском образовании, изучение и обобщение передового опыта преподавания студенческих курсов с использованием информационно-коммуникационных технологий. Анализ результатов эффективности внедрения образовательной и информационной среды проведен по кафедрам фтизиатрии и пульмонологии, гистологии, цитологии и эмбриологии, медицинской физики, биофизики и высшей математики и аналитической химии. Результаты. В статье представлены некоторые результаты работы преподавателей по разработке и использованию информационнообразовательной среды в контексте непрерывного образования современного информационного общества. Информационно-образовательная среда, обеспечивающая взаимодействие преподавателей и студентов в классе через интерактивные формы общения на платформе edХ, способствует оптимизации учебного процесса. Обоснованы основные принципы обеспечения инновационных подходов, методов, технологий единого информационно-образовательной среды высшего учебного медицинского учреждения. Подчеркнута необходимость раскрытия опыта высших учебных заведений по созданию информационно-образовательной среды, как составляющей оптимизации учебного процесса студентов. Опыт использования новой формы обучения подтвердил простоту и интерактивность взаимодействия студента и преподавателя, дает широкие возможности для организации учебной деятельности, позволяя студенту самостоятельно моделировать свой процесс обучения, а также новые формы контроля учебной деятельности. Заключение. По нашему мнению, online курсы на платформе edX способствуют оптимизации учебного процесса вуза. Перспективой дальнейшей работы мы видим в разработке и внедрению в учебный процесс online курсов для самостоятельной работы студентов на платформе edX.
Оптимізація навчального процесу вищих навчальних медичних закладів через інформаційно-освітнє середовище.
Оптимизация учебного процесса высших учебных медицинских заведений через информационно-образовательную среду.
Keywords: informational and educational environment; optimization of the educational process; professional education; innovation-educational technology; інформаційно-освітнє середовище; оптимізація навчального процесу; професійне навчання; інноваційно-освітня технологія; информационно-образовательная среда; оптимизация учебного процесса; профессиональное обучение; инновационно-образовательная технология